False-positive Aspergillus galactomannan immunoassays associated with intravenous human immunoglobulin administration. (November 2020) - Liu, W.-D.; Lin, S.-W.; Shih, M.-C.; Su, C.-L.; Wang, Y.-W.; Lin, S.-C.; Lee, Y.-F.; Huang, H.-H.; Chou, W.-C.; Wu, U.-I.; Chen, Y.-C.; Chang, S.-C.
Abstract: Objectives: Evidence of false-positive galactomannan enzyme immunoassay (GM-EIA) results associated with intravenous immunoglobulin (IVIG) administration is scarce. Here, we aimed to determine the false-positive rate of GM-EIA after IVIG administration and to identify the related factors. Methods: Standard GM-EIA was performed using diluted and pure human IVIG samples with and without heat treatment. We also included adult patients who had at least one GM-EIA result within 1 week of IVIG administration for analysis. Those who had prior invasive aspergillosis within 1 year before IVIG therapy were excluded. The clinical characteristics and galactomannan index (GMI) kinetics between patients with false-positive and true-positive GMI were compared. Results: All diluted and pure IVIG samples tested positive for GM. Heat treatment resulted in the considerable elevation of GMI. Of 48 patients with positive GM-EIA results within 1 week of IVIG administration, 22 (45.8%) were considered to have false-positive antigenaemia (false-positive group, FPG). After the completion of IVIG administration, a decline in GMI was observed in all FPG patients but in only 18 out of 26 patients (69.2%) with true-positive results (true-positive group, TPG). By 7, 14, and 18 days of IVIG administration, GMI reverted to negative values in 7/15 (46.7%), 18/20 (90%) and 22/22 (100%) FPG patients, respectively, and 6/24 (25%), 14/24 (58.3%), and 16/26 (61.5%) of TPG patients, respectively. The TPG was more likely to have two or more consecutively positive GMIs after IVIG administration than the FPG (adjusted odds ratio, 9.01; 95% confidence interval, 1.99–40.9). Conclusions: IVIG treatment may produce false-positive GM-EIA results. A positive GMI among patients receiving human IVIG should be interpreted with caution.